Types of Consciousness: The Diversity Problem - Montemayor, Carlos (Frontiers in Systems Neuroscience, 2021)
Consciousness research has a cognitive-diversity problem. Any view that holds that attention is either necessary for consciousness or that attention precedes conscious awareness confronts the difficulty that the theoretical categorization of attention is as diverse as the categorization of intelligent cognition, but consciousness is typically referred to as a single and unified capacity. On the one hand, we have a multiplicity of kinds of attention. On the other hand, we use a monolithic “phenomenal” notion of consciousness to define the dependency of consciousness on all these diverse kinds of attention. Since attention is defined in terms of a diverse variety of functions, a lot more needs to be said with respect to the claim that attention is either necessary for consciousness or that attentional processing precedes conscious awareness. Is this dependency based on the diverse cognitive functions of attention? If so, why conceive of consciousness as a single informationally unified cognitive capacity? What does the multiplicity of kinds of attention entail for consciousness research? This is the “diversity problem.” This paper argues that consciousness should be also considered as a diverse set of capacities, based on the diversity of attention. While we have the intuition that consciousness is a unified perspective, the paper shows that consistency demands this diverse approach. Since research on attention distinguishes a wide range of functions and levels of cognitive processing, the dependency of consciousness on attention entails diverse conscious capacities and diverse types of awareness beyond the distinctions between being awake, dreaming, and being minimally conscious.